Dielectric aging of Cr-doped PZT ceramics - P. Ketsuwan (2018)
The aging of dielectric properties of Cr-Doped Pb(Zr0.5 2 Ti 0.48 )O 3 were investigated. The composition of Pb(Zr0.5 2 Ti 0.48 )O 3 with 0.1, 0.2, 0.4, 0.6, 1.0 and 3.0 mol% of Cr 2 O 3 addition were prepared by conventional mixed oxide technique. The aging has been measured at room temperature after quenching from high temperatures above the Curie temperature. The dielectric aging of all compositions revealed relaxor aging behavior. The aging rate of stable stage obeyed a logarithmic time dependence, while the aging rate decreased with increasing Cr 2 O 3 at low concentration (0.1-0.6). Further increase in Cr 2 O 3 concentration, the aging rate turned to increase. © 2013 Copyright Taylor and Francis Group, LLC.